NECROTIZING PANCREATITIS: DESCRIPTION OF VIDEOSCOPIC ASSISTED RETROPERITONEAL DEBRIDEMENT (VARD) TECHNIQUE WITH COVERED METALLIC STENT - HOUGHTON, Eduardo J. (Arq Bras Cir Dig, 2018)
BACKGROUND : Acute pancreatitis is the third most common gastrointestinal disorder requiring hospitalization in the United States, with annual costs exceeding $2 billions. Severe necrotizing pancreatitis is a life-threatening complication developed in approximately 20% of patients. Its mortality rate range from 15% in patients with sterile necrosis to up 30% in case of infected one associated with multi-organ failure. Less invasive treatment techniques are increasingly being used. These techniques can be performed in a so-called step-up approach. AIM: To present the technique for videoscopic assisted retroperitoneal debridement (Vard technique) with covered metallic stent in necrotizing pancreatitis. METHOD: A guide wire was inserted through the previous catheter that was removed in the next step. Afterwards, the tract was dilated over the guide wire. Then, a partially covered metallic stent was deployed. A 30 degrees laparoscopic camera was inserted and the necrosis removed with forceps through the expanded stent under direct vision. Finally, the stent was removed and a new catheter left in place. RESULT : This technique was used in a 31-year-old man with acute pain in the upper abdomen and diagnosed as acute biliary pancreatitis with infected necrosis. He was treated with percutaneous drains at weeks 3, 6 and 8. Due to partial recovery, a left lateral VARD was performed (incomplete by fixed and adherent tissue) at 8(th) week. As the patient´s inflammatory response was reactivated, a second VARD attempt was performed in three weeks later. Afterwards, patient showed complete clinical and imaging resolution. CONCLUSIONS : Videoassisted retroperitoneal necrosectomy using partially covered metallic stent is a feasible technique for necrotizing pancreatitis.